Digitalisasi Layanan Asesmen Konseling Berbasis Neuro-linguistic Programming Dengan Model ADDIE Di SMK Negeri 1 Kademangan Blitar - Muchamad Saiful Muluk; Rafika Akhsani; Ibnu Athaillah; Moch. Kholil (Universitas Islam Negeri Madura, 2024)
Counseling services are an integral part of education in helping students fulfill their developmental tasks and solve problems that hinder them. However, there are problems that hinder the performance of counseling teachers, including the proportion of counseling teachers' duties exceeding the limit, the complexity of students' problems, the conventional counseling service process, and the lack of documentation of the counseling process. This requires a solution, one of which is the digitization of counseling services. The focus of this research is the development of a neuro-linguistic programming (NLP) based counseling service application at SMK Negeri (SMKN) 1 Kademangan Blitar. The research procedure uses the ADDIE model (analysis, design, development, implementation and evaluation). Data collected by forum group discussion, interview, observation and documentation. The results showed that the developed counseling service application was able to detect the tendency of the counselee's modality and determine the sub modality map quickly and accurately. This makes it easier for counselors to carry out the stages of diagnosis, prognosis, treatment, evaluation and follow-up of counseling process, as well as documenting the counseling record. Based on the results of the application testing and implementation, counseling teachers feel helped by the digital counseling service application.